BALANCING JUDICIAL ACTIVISM AND RESTRAINT IN INDONESIA’S CONSTITUTIONAL COURT - Ahmad; Apdan; Mohammad Nur Kholis (Proceeding International Conference on Social Sciences, 2026)
This study examines the trends in judicial activism and restraint in the Indonesian Constitutional Court's judicial review rulings, as well as the consequences for constitutional democracy. The study looks at 15 significant rulings from 2010 to 2024 using a qualitative doctrinal approach and case-based jurisprudential analysis. The findings demonstrate that while the Constitutional Court exercises judicial activism to uphold citizens' constitutional rights and reinforce the idea of checks and balances, it also exercises judicial restraint when it comes to matters of public policy. These results highlight the necessity of bolstering the processes for carrying out rulings and striking a dynamic balance between judicial activism and caution. The report suggests updating the Constitutional Court Law, standardizing the reasoning behind decisions, raising public awareness, and enhancing cooperation between the House of Representatives, the Constitutional Court, and civil society.